2016
DOI: 10.1021/jacs.6b03166
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of Quantum Confined Single Crystal CsPbBr3 Nanosheets with Lateral Size Control up to the Micrometer Range

Abstract: We report the nontemplated colloidal synthesis of single crystal CsPbBr3 perovskite nanosheets with lateral sizes up to a few micrometers and with thickness of just a few unit cells (i.e., below 5 nm), hence in the strong quantum confinement regime, by introducing short ligands (octanoic acid and octylamine) in the synthesis together with longer ones (oleic acid and oleylamine). The lateral size is tunable by varying the ratio of shorter ligands over longer ligands, while the thickness is mainly unaffected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
525
2
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(550 citation statements)
references
References 28 publications
22
525
2
1
Order By: Relevance
“…In addition, they have also shown that the lateral size of the quantum-confined CsPbBr 3 nanoplatelets (thickness~3 nm) can be controlled up to the micrometer range by varying the ratio of shorter ligands (octanoic acid and octylamine) to longer ligands (oleic acid and oleylamine), while maintaining their thickness and, to a large degree, the optical properties. 93 Single-particle emission of perovskite NCs Most of the studies discussed above have been performed on ensembles of perovskite NCs. However, single-particle measurements are sometimes necessary, in order to obtain accurate correlations between their optical properties and size/morphology.…”
Section: Quantum Confinement In Perovskite Ncsmentioning
confidence: 99%
“…In addition, they have also shown that the lateral size of the quantum-confined CsPbBr 3 nanoplatelets (thickness~3 nm) can be controlled up to the micrometer range by varying the ratio of shorter ligands (octanoic acid and octylamine) to longer ligands (oleic acid and oleylamine), while maintaining their thickness and, to a large degree, the optical properties. 93 Single-particle emission of perovskite NCs Most of the studies discussed above have been performed on ensembles of perovskite NCs. However, single-particle measurements are sometimes necessary, in order to obtain accurate correlations between their optical properties and size/morphology.…”
Section: Quantum Confinement In Perovskite Ncsmentioning
confidence: 99%
“…2,[5][6][7] Compared to classical Cd-based chalcogenide quantum dots (QDs), CsPbX 3 (X = Cl, Br, I) offer a very broad and easily adjustable composition versatility together with ample options for shape control, which allow tuning of their emission wavelength throughout the whole visible spectrum. [8][9][10][11][12][13][14] Among other applications, such highly luminescent and spectrally tunable NCs are ideally suited to produce monochromatic and white LEDs (WLEDs). 15 In this regard, CsPbX 3 NCs have been utilized as the emissive layer in electroluminescent monochromatic and color conversion QD-LEDs showing exceptionally narrow emission bandwidths and thus high color quality in devices.…”
Section: Introductionmentioning
confidence: 99%
“…12,16,17 The size and shape of the particles are important factors determining the resulting optical properties because of their influence on the bandgap, known as the quantum size effect. 18,19 CsPbX 3 nanocrystals are frequently synthesized in the form of nanocubes, while two-dimensional morphologies such as nanosheets and nanoplatelets are also obtained.…”
Section: Influence Of Organic Ligands On Particle Morphologies Of Cspmentioning
confidence: 99%